Efficacy and Safety of Etomidate in Comparison with Propofol or Midazolam as Sedative for Upper Gastrointestinal Endoscopy - Jae Hyun Kim; Sanghwan Byun; Youn Jung Choi; Hye Jung Kwon; Kyoungwon Jung; Sung Eun Kim; Moo In Park; Won Moon; Seun Ja Park (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims In this study, we compared the efficacy and safety of etomidate with those of propofol or midazolam for the maintenance of sedation during endoscopy. Methods The study enrolled patients who underwent sedative endoscopy in our hospital and divided them into three groups. Patients in each group were administered midazolam as induction therapy and were subsequently administered either midazolam (M + M group), propofol (M + P group), or etomidate (M + E group) as maintenance medication. The primary outcome was overall cardiovascular and respiratory adverse events. Results In total, 105 patients who underwent sedative endoscopic examination were enrolled. The outcomes related to the procedure and sedation were not significantly different among the groups. Overall cardiovascular and respiratory adverse events were observed in 9 patients (25.7%) in the M + M group, 8 patients (23.5%) in the M + P group, and 10 patients (27.8%) in the M + E group. The logistic regression analysis revealed that etomidate use was not an independent risk factor for overall cardiovascular and respiratory adverse events. Conclusions The outcomes following the use of etomidate for maintenance after induction with midazolam for sedation in upper gastrointestinal endoscopy were not inferior to those following midazolam or propofol use from the perspectives of safety and efficacy.